2003
DOI: 10.2337/diacare.26.4.1147
|View full text |Cite
|
Sign up to set email alerts
|

Oral Magnesium Supplementation Improves Insulin Sensitivity and Metabolic Control in Type 2 Diabetic Subjects

Abstract: OBJECTIVE -To determine whether oral magnesium supplementation (as magnesium chloride [MgCl 2 ] solution) improves both insulin sensitivity and metabolic control in type 2 diabetic subjects with decreased serum magnesium levels. RESEARCH DESIGN AND METHODS-This study was a clinical randomized double-blind placebo-controlled trial. A total of 63 subjects with type 2 diabetes and decreased serum magnesium (serum magnesium levels Յ0.74 mmol/l) treated by glibenclamide received either 50 ml MgCl 2 solution (conta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

16
235
6
7

Year Published

2005
2005
2015
2015

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 367 publications
(264 citation statements)
references
References 34 publications
16
235
6
7
Order By: Relevance
“…It is interesting that the induction of Mg deficiency has been shown to reduce insulin sensitivity in individuals without diabetes, whereas Mg supplementation during a 4-wk period has been shown to improve glucose handling in elderly individuals without diabetes (18,24). In patients with type 2 diabetes, oral Mg supplementation during a 16-wk period was suggested to improve insulin sensitivity and metabolic control (25). The mechanisms whereby hypomagnesemia may induce or worsen existing diabetes are not well understood.…”
Section: Hypomagnesemia and Diabetes: Cause And Effectmentioning
confidence: 99%
“…It is interesting that the induction of Mg deficiency has been shown to reduce insulin sensitivity in individuals without diabetes, whereas Mg supplementation during a 4-wk period has been shown to improve glucose handling in elderly individuals without diabetes (18,24). In patients with type 2 diabetes, oral Mg supplementation during a 16-wk period was suggested to improve insulin sensitivity and metabolic control (25). The mechanisms whereby hypomagnesemia may induce or worsen existing diabetes are not well understood.…”
Section: Hypomagnesemia and Diabetes: Cause And Effectmentioning
confidence: 99%
“…30 -35 Although it has been suggested that Mg 2ϩ deficiency contributes to the induction of diabetes and its associated complica- , and variations in study population complicate these trials. 30,[37][38][39] …”
Section: Treatment Of Hypomagnesemiamentioning
confidence: 99%
“…(Mori et al, 1993). Magnesium plays a role in genomic stability and DNA repair (Hartwig, 2001;Larsson et al, 2005) and may reduce hyperinsulinaemia (Paolisso et al, 1992;Rodriguez-Moran and Guerrero-Romero, 2003), a risk factor for colorectal cancer (Giovannucci, 1995;Schoen et al, 1999). In the Netherlands Cohort Study (NLCS), we investigated colorectal cancer in both sexes in relation to magnesium intake, particularly in overweight subjects, given the suggested beneficial effects of magnesium on insulin resistance (Fung et al, 2003).…”
mentioning
confidence: 99%